The access network: Supporting the construction of social justice physics identities through student partnerships - Reinholz, Daniel Lee; Corrales, Adriana; Stone-Johnstone, Amelia (International Journal for Students as Partners, 2019)
This paper explores the intersections of Students as Partners (SaP) and identity development. While identity and sense of belonging are known to be key factors for predicting success and persistence in STEM, less is known about how student partnerships can provide space for students to develop their identities. To explore this space, we focus on the Access Network, a coalition funded by the National Science Foundation (NSF) of student-run programs that aims to improve equity in the physical sciences. Qualitative interviews with six student participants showed how SaP created opportunities for students to develop social justice physics identities, which allowed them to bridge traditional notions of what it means to be a physicist with their own social justice commitments. This paper contributes to the rapidly growing SaP literature by studying student partnerships at the scale of a national network of institutions, which contrasts studies that focus on more localized contexts, such as teaching and learning in a single classroom.